Comparación de la reformas de los sistemas de salud en Colombia y Costa Rica en su dimensión política (2011)
ABSTRACT: To analyze the political dimension of the reform of the health systems of Colombia and Costa Rica over the period 1990 to 2009. Methodology: we conducted an investigation using the methodology of comparison between countries (Cross National). There was a systematic use of comparative data from Colombia and Costa Rica, looking for similarities and differences between the two countries. Results: it was showed the similarity in the political and administrative establishment of the two States under review, also we could see that much of the course and implement reforms that make health systems are highly conditioned by the participation of civil society in the reform process, as well as the guidelines issued by international financial organizations. Conclusions: Colombia has a mixed insurance system regulated and market-linked private sector. Costa Rica has instead integrated public system, linked for the purposes of the state, eminently universal, supported by civilian actors as a fundamental pillar who endorse or reject the decisions on health sector reforms, with limited involvement of private sector. The rectory is assumed by the State through the Ministry of Health, which protects and enforces the rights and creates policies to increase the level of health of the population so that results in improved living standards.